A systematic comparison of roundtrip software engineering approaches applied to UML class diagram - Rosca, D. (2021)
Model-based software engineering contemplates several software developments approaches in which models play an important role. One such approach is round-trip engineering. The objective of this paper is to benchmark the comparative analysis of the round-trip engineering capability of three modelling tools: Papyrus, Modelio and Visual Paradigm. The conclusions drawn throughout the paper will answer the question: How effective are current code generation tools for documenting application evolution? Throughout the discussion, we have pointed out several improvements that these UML modelling tools have recently brought to the discussion. We have also proposed some improvements that we consider desirable to improve Roundtrip Engineering approaches pointing out possible directions and solutions.